Effect of Storage Conditions on Seed Viability and Vigour of Quinoa (Chenopodium quinoa Willd.) Variety Himshakti - AXAY BHUKER; VS MOR; MS PUNEETH RAJ; JHABARMAL SUTALIYA; MS HARISH (Seed Research, 2025)
Quinoa (Chenopodium quinoa), a nutrient-rich pseudocereal, is increasingly valued worldwide; however, limited data exist on its seed storability under typical handling conditions. This study assessed the viability and vigor of freshly harvested seeds of the variety ‘Himshakti’ stored in polythene bags under controlled (4°C and 6°C, 30±5% RH) and ambient conditions over eight months. Initial germination was below 50%, and a sharp decline was observed under ambient storage—from 41% to 6%. In contrast, seeds stored at 4°C retained 37% germination. Superior seedling traits and vigor indices were recorded under cooler conditions, with seeds at 4°C showing maximum seedling length (11.90 cm), dry weight (1.09 mg), vigor index-I (443.1), and vigor index-II (40.42). Seeds stored under ambient conditions showed the poorest performance across all parameters. The study concludes that storing quinoa seeds at 4°C temperature and 30±5% RH in polythene bags significantly preserves seed quality over time.